Chapter 3 Digital Inquiry into Emerging Issues of Public Concern Controversy mapping in a Swedish school context - Mäkitalo, Åsa (Taylor & Francis, 2019)
Designs for Experimentation and Inquiry examines how digital media is reconfiguring the established worlds of research, education, and professional practice. It reflects on the theoretical, methodological, and ethical issues shaping contemporary engagements with digital learning and offers insights for both analysing and intervening in digital learning practices. This insightful volume fills a gap in the current literature by bringing together experiences from Sociocultural Studies of Learning, Science and Technology Studies, and Design Studies. Each chapter is an innovative case study, examining a different aspect of digital media's role in research, education and professional practice.